Numerical Investigation on Flow-Field Characteristics towards Removal of Free-Water by A Separator with Coalescing Plates - Qi, Xiangdong; Zhang, Hongqi; Sun, Xitong; Wang, Zhihua (Journal of Advances in Applied & Computational Mathematics, 2023)
The produced water-containing polymer brings new challenges to oil-water separation in oilfield production, yet separators with coalescing plates to remove free water have been playing an active role. In this paper, the flow-field characteristics of polymer-laden produced water in a separator with coalescing plates are analyzed using computerized mathematical methods to investigate the effects with a water content of 55%, 70%, and 85%, flow rate of 3500 m3/d, 4800 m3/d, and 6000 m3/d, and duration time of 20 min, 40 min, and 60 min on flow-field properties and separating efficiency are studied. The results show that the separating efficiency is positively correlated with water content and duration time, and duration time has the greatest improvement to the separating efficiency, but the enhancement of flow rate may reduce the separating efficiency. It is also observed that the separation efficiency of free-water reached 70.9% and the water content at the oil outlet of the separator reached 20.4% at a duration time of 60 min, when the contained polymer concentration and water content in the oil-water mixture are 500 mg/L and 70%, respectively.